(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This study investigates the effects of transient inlet velocity on the hydrodynamic performance, blade loading, and wake dynamics of a three-bladed horizontal axis tidal turbine (HATT). The turbine geometry corresponds to that used in experimental studies at IFREMER, enabling a robust comparison with empirical data. Advanced computational fluid dynamics (CFD) simulations use the Improved Delayed Detached Eddy Simulation (IDDES) turbulence model within ANSYS FLUENT to capture the complex unsteady flow phenomena inherent to tidal energy systems. The turbulence closure model utilized, Detached Eddy Simulation (DES), combines the strengths of the k-ω Shear Stress Transport (SST) model and Large Eddy Simulation (LES). The k-ω SST model is effective at resolving flow in near-wall regions, capturing small-scale turbulent structures, while LES is employed to accurately model large, anisotropic turbulent eddies in the outer flow domain. This hybrid approach ensures a comprehensive representation of the multiscale turbulence dynamics encountered by tidal turbines. A time-dependent velocity profile is imposed at the inlet boundary, representing the time-varying characteristics of turbulent tidal flows. This transient velocity captures realistic velocity fluctuations, offering an accurate simulation of the transient hydrodynamic environment. A sliding mesh technique is used to simulate the rotational motion of the turbine blades, allowing precise analysis of blade-flow interactions and the associated unsteady hydrodynamic loading. The study provides detailed analyses of transient forces on turbine blades, including pressure and viscous contributions, through force monitoring and surface integration techniques. Sectional load distributions are investigated to identify periodic variations in blade loading, revealing insights into the impact of unsteady flow on the hydrodynamic performance of tidal turbines. Furthermore, wake dynamics are investigated to characterize velocity deficits and turbulence intensity downstream, which are critical for understanding turbine spacing and array design. The simulation results are compared with those obtained from Reynolds-Averaged Navier-Stokes (RANS) simulations using the k-ω SST model and experimental data from IFREMER. The comparisons highlight the superiority of DES in resolving unsteady flow features and provide validation for the numerical model. In conclusion, this study offers a comprehensive understanding of the transient hydrodynamic effects on tidal turbine performance, advancing the optimization of blade design and operational strategies. The findings have significant implications for improving the reliability and efficiency of tidal energy systems in real-world operating conditions.